Evaluation of Anxiety Levels of Bintang Prima SGO Karate Dojo Athletes - Fajrial, Jul; Putra, Sukardi; Wahdi, Arif; Karimuddin, Karimuddin; Isdarianti, Novi Lidya (Musamus Journal of Physical Education and Sport (MJPES), 2023)
Objectives. This study aimed to determine the anxiety levels of Dojo Bintang Prima SGO karate athletes during competitions using a descriptive quantitative approach. Anxiety negatively impacts an athlete's performance and was found to be high among the observed athletes. Materials and methods. The study involved 15 athletes from the Bintang Prima SGO Karate Dojo. In this study, the entire population was considered as the sample or the total side. The data was collected using a closed questionnaire known as SCAT (Sport Competition Anxiety Test). The questionnaire comprised 15 Likert scale questions, where participants had to choose their answers based on their feelings or experiences before competing. The answer choices were "Never" with a value of 1, "Sometimes" with a value of 2, and "Often" with a value of 3. Results. According to the research, the anxiety level of karate athletes from Dojo Bintang Prima SGO was 19.6, which falls under the "Medium Anxiety Level" category. Out of all athletes, four (27%) were in the "Low Anxiety" category, ten (67%) were in the "Moderate Anxiety" category, and only one athlete (6%) was in the "High Anxiety" category. Conclusion. Through the research data that has been explained, it can be concluded that the anxiety level of Dojo Bintang Prima SGO karate athletes is 19.6, which is in the Medium Anxiety Level category.